Pengaruh Keberadaan Apoteker terhadap Mutu Pelayanan Kefarmasian di Puskesmas Wilayah Kabupaten Banyumas - Hanggara, Rr. Shinta Lian; Gibran, Nabial Chiekal; Kusuma, Anjar Mahardika; Galistiani, Githa Fungie (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Due to complexity enhancement of health care services, pharmacists are required to provide their orientation to the patient.The objective of the study are to evaluate the pharmaceutical standard prosedures and measuring the effect of the pharmacist’s presence on the pharmacy services quality in the Community Health Centers (CHCs) of Banyumas districts. The study is an observational analytic categorical through cross sectional approach with colleting data technique is divided into two periods, through observation and structured interviews to the person in charge of pharmaceutical care unit. Based on the analysis, from 38 CHCs it’s found out that 24 (63,16%) CHCs have the pharmaceutical standard procedures and 14 (36,84%) CHCs doesn’t have it. However, of the 39 CHCs, there are 33 (84,61) CHCs that have pharmacist, 2 (6,06%) CHCs were categorized in a moderate quality and 31 (93,94%) of them categorized as having less quality. While the six (15,38%) CHCs that doesn’t have a qualified pharmacist categorized as having less quality. There are the presence of pharmacists towards the availability ofthe pharmaceutical standard prosedures, have p value of 0.363 (p>0.05) and the pharmaceutical services checklist with p value of 1.00 (p>0.05)at CHCs of Banyumas districts. Conclusionis pharmaceutical services in Banyumas district aren’t running optimally because presence of pharmacists hasn’t improve the quality